Solutions for humanity on how to conserve insects. (February 2020) - Samways, Michael J.; Barton, Philip S.; Birkhofer, Klaus; Chichorro, Filipe; Deacon, Charl; Fartmann, Thomas; Fukushima, Caroline S.; Gaigher, René; Habel, Jan C.; Hallmann, Caspar A.; Hill, Matthew J.; Hochkirch, Axel; et al.
Abstract: The fate of humans and insects intertwine, especially through the medium of plants. Global environmental change, including land transformation and contamination, is causing concerning insect diversity loss, articulated in the companion review Scientists ' warning to humanity on insect extinctions . Yet, despite a sound philosophical foundation, recognized ethical values, and scientific evidence, globally we are performing poorly at instigating effective insect conservation. As insects are a major component of the tapestry of life, insect conservation would do well to integrate better with overall biodiversity conservation and climate change mitigation. This also involves popularizing insects, especially through use of iconic species, through more media coverage, and more inclusive education. Insect conservationists need to liaise better with decision makers, stakeholders, and land managers, especially at the conceptually familiar scale of the landscape. Enough evidence is now available, and synthesized here, which illustrates that multiple strategies work at local levels towards saving insects. We now need to expand these locally-crafted strategies globally. Tangible actions include ensuring maintenance of biotic complexity, especially through improving temporal and spatial heterogeneity, functional connectivity, and metapopulation dynamics, while maintaining unique habitats, across landscape mosaics, as well as instigating better communication. Key is to have more expansive sustainable agriculture and forestry, improved regulation and prevention of environmental risks, and greater recognition of protected areas alongside agro-ecology in novel landscapes. Future-proofing insect diversity is now critical, with the benefits far reaching, including continued provision of valuable ecosystem services and the conservation of a rich and impressive component of Earth's biodiversity. Highlights: Human and insect well-being intertwine. Philosophical, psychological, and scientific basis of insect conservation is robust. Solutions are available for averting further insect decline. Effective localized principles and solutions must now be actioned globally. Engaging civil society on the value of insects for human well-being is urgent.